The BMP antagonist gremlin 1 contributes to the development of cortical excitatory neurons, motor balance and fear responses - Ichinose, Mari (Development, 2021)
Bone morphogenetic protein (BMP) signaling is required for early forebrain development and cortical formation. How the endogenous modulators of BMP signaling regulate the structural and functional maturation of the developing brain remains unclear. Here, we show that expression of the BMP antagonist Grem1 marks committed layer V and VI glutamatergic neurons in the embryonic mouse brain. Lineage tracing of Grem1-expressing cells in the embryonic brain was examined by administration of tamoxifen to pregnant Grem1creERT; Rosa26LSLTdtomato mice at 13.5 days post coitum (dpc), followed by collection of embryos later in gestation. In addition, at 14.5 dpc, bulk mRNA-seq analysis of differentially expressed transcripts between FACS-sorted Grem1-positive and -negative cells was performed. We also generated Emx1-cre-mediated Grem1 conditional knockout mice (Emx1-Cre;Grem1(flox/flox)) in which the Grem1 gene was deleted specifically in the dorsal telencephalon. Grem1(Emx1cKO) animals had reduced cortical thickness, especially layers V and VI, and impaired motor balance and fear sensitivity compared with littermate controls. This study has revealed new roles for Grem1 in the structural and functional maturation of the developing cortex.